CORPUS LINGUISTIC RESEARCH: ANALYZING ADVERB OF PLACE IN "THE HOBBIT" NOVEL BY J.R.R. TOLKIEN - Rizky Amalia Ardhani (EJI (English Journal of Indragiri) : Studies in Education, Literature, and Linguistics, 2021)
One part of speech that is usually in various works of literature is an adverb. Adverbs are important because used to provide a further description of a verb. Adverb will explain how an incident took place. This article will take the theme from the adverb of place. The function of the adverb of place in sentence structure is to express where an event occurs. Adverbs of place are usually after an object or main verb. This study examines the frequency and usage patterns of the adverb of place in J. R. R. Tolkien's novel The Hobbit. The Hobbit is an epic fantasy adventure novel by world-renowned author J.R.R. Tolkien. In a short time, this fantasy novel series immediately received a positive response from readers in England and America before spreading to all corners of the world. This novel was chosen as the data source because the sentences contained many adverbs of place.